Reproductive health equity: demystifying unmet need for family planning among young women in Uttar Pradesh - Punit Mishra (Contraception and Reproductive Medicine)
Abstract Background The unmet need for contraception among adolescent women in India is a significant public health concern, contributing to unintended pregnancies and abortions. This paper seeks to examine the regional variations and factors driving rural–urban disparities in unmet family planning needs in Uttar Pradesh (UP), India’s most populous state, where the total unmet need among adolescents is as high as 19%. Methods The study is based on 11,018 adolescent women from the recent round of India’s DHS, NFHS-5 (2019–21). To fulfil the study’s objective, Multilevel logit model and Oaxaca Blinder Decomposition was applied. Results The Multilevel logit model results show statistically significant variations at community and district level, implying a strong presence of unobserved factors affecting the unmet demand. Oaxaca decomposition results show that difference in rural and urban adolescent unmet need is explained by factors like wealth, religion and intra-state regions. Conclusion The results call for the need to implement culturally appropriate reproductive and sexual health literacy programs to increase uniform access to modern contraception and to raise women’s autonomy in the state of Uttar Pradesh.